Low preoperative selenium is associated with post-operative atrial fibrillation in patients having intermediate-risk coronary artery surgery - McDonald, C; Fraser, J; Shekar, K; Clarke, A; Coombes, J; Barnett, A; Pearse, B; Fung, L (European journal of clinical nutrition, 2016)
Background/objectives: Post-operative atrial fibrillation (POAF) is a frequent complication of cardiac surgery. Oxidative stress and reduced antioxidant function have major roles in its development. Selenium is a key to normal antioxidant function, and levels are often low before cardiac surgery. This study investigated whether low preoperative selenium levels were associated with POAF in cardiac surgical patients. Subjects/methods: Using the Society of Thoracic Surgeons (STS) Mortality risk score, 50 patients having primary coronary artery bypass grafts (CABG) surgery were divided into two groups: (i) low-risk group (STS ⩽0.5%; n =26) and (ii) intermediate-risk group (STS ⩾2.0%; n =24). Plasma levels of selenium, glutathione peroxidase (GPx) and malondialdehyde (MDA) were measured in all patients at anaesthetic induction, after aortic cross-clamp removal, 3 h post cardiopulmonary bypass and on post-operative days 1 and 5. Multiple logistic regression was used to assess whether selenium levels were associated with POAF development. Results: Seventeen patients developed POAF (14 patients in the intermediate-risk group and 3 patients in the low-risk group). Preoperative selenium was lower in patients who developed POAF compared with those with normal sinus rhythm (0.73±0.16 vs 0.89±0.13 μmol/l, P =0.005), and this was independently associated with POAF (PR 0.32; 95% confidence credible interval (95%cI) 0.06–0.85, P =0.016). Regardless of POAF, preoperative selenium was lower in the intermediate-risk patients than in the low-risk patients (0.77±0.15 vs 0.89±0.14 μmol/l; P =0.004). Conclusions: Intermediate-risk patients with low preoperative selenium levels may be at a greater risk of developing POAF following CABG. This raises the question of whether selenium supplementation in select cardiac surgical patients may reduce their POAF risk.